Estudio de la variabilidad temporal y espacial de la pérdida de suelo en la dehesa (Extremadura, SO España) mediante lluvia simulada - Ceballos Barbancho, A.; Schnabel, S.; Cerdá, A. (Geographicalia, 2016)
The main objective of this paper is to study the influence of the seasonal variability of the antecedent conditions in soil losses in a dehesa ecosystem, as well as an approach to its spatial variability. The experimental layout includes forty rainfall simulation experiments carried out in two different situations: first on dry conditions, with degraded vegetation, and, second on wet conditions, with an important vegetation cover. The results indicate that the highest sediment concentrations are located in situations with bare soils, due to the effect of the drought and the soil removed by grazing animals. The control of the process depends more to the sediment available on the soil surface than to the runoff transport capacity. From an spatial point of view, it highlights the contrast between the low losses registered in the valley bottoms and the highest values measured in the areas more frequented by the livestock, where the degradation of the vegetation cover and the removal of the soil material are continuous. Finally, although the rate of soil loss in the dehesa is low, it is important from a qualitative point of view because it affects to the most fertile horizon in the soil profile.
Keywords: soil loss; sediriient concentration; season; runoff; rainfall simulation; dehesa